Fighting words : religion, violence, and the interpretation of sacred texts - Renard, John, 1944- (University of California Press, 2012)
One of the critical issues in interreligious relations today is the connection, both actual and perceived, between sacred sources and the justification of violent acts as divinely mandated. Fighting Words makes solid text-based scholarship accessible to the general public, beginning with the premise that a balanced approach to religious pluralism in our world must build on a measured, well-informed response to the increasingly publicized and sensationalized association of terrorism and large-scale violence with religion. In his introduction, Renard provides background on the major scrip.